WHAT IS VALUABLE IN THE ACADEME: CORPUS-BASED ANALYSIS - Vodyanitskaya, Albina; Yaremenko, Vera (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The paper focuses on the corpus-based analysis of academic discourse values. The research aim is to reveal how teachers transmit academic discourse values through their everyday interactions with students (during lectures, seminars) and to reveal, which values are relevant for the students (based on the analysis of their essays, research papers and some such). The research relies on corpus-based approach and primary methods used are a semantic analysis and a context analysis as well as definition analysis of evaluative means. The research results have revealed that various values play important role in academic interactions and shape the image of the academe – on the local as well as on the global scale. The study of the contexts containing the word valuable in British National Corpus (Davis, 2008-), British Academic Spoken English (Nesi, & Thompson, 2000-), British Academic Written English (Nesi, 2008-), Corpus of Russian Student Texts (Rakhilina, Zevakhina, & Dzhakupova, 2013-) and Michigan Corpus of Academic Spoken English (2002-) has revealed that the values of academic discourse can be subdivided into six domains: emotional, cognitive, educational, research-related, academic life-related, topic- / area-related. The further applicability of research findings manifests itself in various avenues of research: linguistics (evaluative means), axiology (cross-disciplinary study of values), teaching practices (academic discourse genres) and others.